2007
DOI: 10.1177/0145721707304079
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Living With Diabetes Women's Day-to-Day Experiences

Abstract: Purpose-The purpose of this study is to understand the feelings of depression, anxiety, and anger experienced by women with type 2 diabetes and the impact these feelings have on their overall quality of life.Methods-Four focus groups (2 white, 2 African American) were conducted by ethnically matched professional moderators. Sessions were audiotaped, and transcriptions were analyzed using an inductive approach. Forty-one women (mean age, 55.6 years; SD = 7.9) who had type 2 diabetes for an average of 8.7 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 39 publications
6
97
1
4
Order By: Relevance
“…Regarding the PSF group, the results of this study showed that, despite women attending more to health services, they had more chance of having a worse quality of life. This data corroborates with the study of Penckofer et al 29 that showed that the overload of responsibility towards support for the family is a factor that contributes to the non effectuation of the selfcare. Krug et al 30 found that marriage and care of children made women stop performing physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the PSF group, the results of this study showed that, despite women attending more to health services, they had more chance of having a worse quality of life. This data corroborates with the study of Penckofer et al 29 that showed that the overload of responsibility towards support for the family is a factor that contributes to the non effectuation of the selfcare. Krug et al 30 found that marriage and care of children made women stop performing physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…the disease and what they actually do are important factors related to how DM2 is integrated into their daily lifestyles (13)(14) . Decisions regarding adherence to dietary restrictions and other care components are highly variable and depend on the immediate situation and how the women rationalize their choices (23) .…”
Section: Concerns With Controlling Diabetes and Dissonancementioning
confidence: 99%
“…Others examine risk factors associated with the development of DM2 (12)(13) ; psychological impact (14)(15) ; family support (9,16) ; quality of life (17) ; treatment adherence (18) ; and metabolic control of DM2 (19) . There is little information, however, on how women integrate or negotiate DM2 healthrelated demands with the needs of their families.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 First, there is robust evidence that individuals experience symptoms of anxiety when they are diagnosed with diabetes. 38,[40][41][42][43][44][45][46] A diagnosis of diabetes may induce anxiety because individuals perceive that the disease will necessitate undesirable lifestyle changes, cause them to lose control over their health, and lead to diabetes-related complications, such as diabetic retinopathy, neuropathy, sexual dysfunction, and macrovascular complications. 47 Second, the daily management of diabetes may result in the experience of anxiety.…”
Section: Introduction Disparitiesmentioning
confidence: 99%